TOLERÂNCIA: FUNDAMENTOS, VISÃO INTERNACIONAL E IMPACTOS NA EDUCAÇÃO - MARGUES, PAULA ANDREATTI (2016)
The aim of the following research is to study the term “tolerance”, raising its theoretical roots: philosophical and historical, as well as political aspects connected to the subject, and its relations to education. The Declaration of Principles on Tolerance by the General Conference of UNESCO (since the determination of the General Assembly of the United Nations in 1992) adopted on November 1995 was concomitant with the preparation of the document Pluralidade Cultural dos PCNs. Thus, besides the relevance of tolerance in the field of education there is a historical dimension of possible impact of the foreign policy over an education policy that should be investigated. This is a qualitative research with documental and bibliographical basis. There is a political relevance involving the subject since its proposition by an agency of the United Nations as important as UNESCO, considering the historical denial of racism and ethnical and religious discrimination practiced until now in public documents regarding the Brazilian educational system, for instance